KABAR MEDAN EFFORTS IN OVERCOMING FAKE NEWS IN SOCIAL MEDIA - Andini Nur Bahri; Yosya Putri Ritonga; Irma Yusriani Simamora; Ahmad Zueni (Fakultas Dakwah dan Komunikasi UIN Sumatera Utara Medan, 2022)
The purpose of this study is to determine how Kabar Medan's online news media efforts are in combating fake news (hoaxes) on social media, as well as what factors are impeding and supporting the Kabar Medan media's efforts in combating fake news on social media. This study uses a descriptive-qualitative approach. Data collection techniques include interviews, observation, and documentation. The results of this study indicate the efforts of the Kabar Medan media in tackling fake news (hoaxes) on social media is a fact-checking platform that is in accordance with the guidelines set by the press council and is systematically implemented by the Kabar Medan media.